Dialogic Reading Strategy for Billingual Child with Language Difficulties - Novara, Annisa Ainina; Widyasari, Pratiwi (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Development of language skills is an important factor in determining children's school readiness. However, problems in language development and communication in early childhood are common. Difficulties in children's language development can have impacts on social engagements, familial dynamics, and scholastic accomplishments. This study aims to assess the efficacy of dialogic reading intervention programs to enhance oral language skills in bilingual children with language difficulties. This study used a quasi-experimental research method, focused on a single participant, utilizing observation for data collection. Quantitative descriptive analysis was employed for data interpretation. The outcomes of this study found that the dialogic reading intervention program was effective in improving children's oral language skills as seen from the number of word responses on pretest and posttest. These findings can provide valuable insights for parents and educators in developing strategies to foster children's oral language skills